Social media and hotel e-marketing in Iran: The case of Parsian International Hotels - Nasihatkon, Banafshen; Kheiri, Jamal; Miralbell, Oriol (Turyzm/Tourism, 2016)
With a quantitative study, this research has aimed to investigate the role of social media in Iranian hotels’ electronic marketing. A questionnaire technique was used on a sample of 140 marketers who work in the Parsian International Hotels’ marketing department. For data evaluation an SPSS program was used. Kolmogorov-Smirnov, Cochran, Regression, Non-standardized coefficients and Standard coefficient tests were carried out. Based on the findings, we can state that social media are still not an important marketing tool for Iranian hotels. Facebook and YouTube are the media which are most used for marketing purposes as videos and photos can be used on these sites more than others. The results show that the marketing abilities of Parsian Hotels improve with the increasing use of social media, but the hotel marketing sector has failed to fully utilize internet opportunity as a marketing tool.